Penyuluhan Pembesaran Benih Kerang Mutiara Pinctada Maxima Untuk Mendukung Minawisata Dan Mata Pencaharian Berlanjutan Bagi Generasi Muda Di Desa Sugian Kecamatan Sambelia, Lombok Timur - Mukhlis, Alis; Abidin, Zaenal; Scabra, Andre Rachmat; Istiqomah, Santun Nur; Mayunita, Alfina Laila; Ramadhan, Devi Aulia; Auliyah, Annisah Nur (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Sugian Village, Sambelia Subdistrict, East Lombok, has great potential for developing pearl oyster (Pinctada maxima) aquaculture-based marine tourism (minawisata). This community service activity aimed to provide counseling to local youth regarding pearl oyster spat rearing as a sustainable alternative livelihood. Through counseling methods involving theoretical and practical sessions, participants gained knowledge about pearl oyster aquaculture techniques, from spat rearing to grow-out. The results of the activity showed a high level of enthusiasm among the youth of Sugian Village to develop pearl oyster aquaculture business and promote it as a new marine tourism attraction. The knowledge gained from this counseling is expected to foster sustainable livelihoods and marine resource conservation in the area.